Identification of anti-lipoarabinomannan antibodies against mannan core and their effects on phagocytosis of mycobacteria by human neutrophils. (January 2022) - Nakayama, Hitoshi; Oshima, Eriko; Hotta, Tomomi; Hanafusa, Kei; Nakamura, Kota; Yokoyama, Noriko; Ogawa, Hideoki; Takamori, Kenji; Iwabuchi, Kazuhisa
Abstract: Mycobacterium tuberculosis (MTB) and M. avium-intracellulare complex (MAC) enter host phagocytes, such as neutrophils through lipoarabinomannan (LAM) binding to pattern-recognition receptors, inducing innate immune responses including phagocytosis. Phagocytosis of mycobacteria by human neutrophils depends on the binding of α(1 → 2)-monomannose branching α(1 → 6)-mannan core of LAM/lipomannan (LM), a common component among mycobacterial species, to lactosylceramide (LacCer)-enriched lipid microdomains. We investigated the binding specificities of several anti-LAM antibodies (Abs) to LAMs/LM and found anti-LAM monoclonal IgMs TMDU3 and LA066 were directed against mannan core. Each IgM showed different binding specificity to mannan core. Confocal and stimulated emission depletion microscopy revealed TMDU3 and LA066 strongly bind to MTB and MAC, respectively. Flow cytometric analysis revealed human neutrophils do not express Dectin-2, DC-SIGN or mannose receptor. Furthermore, neutrophil phagocytosis of mycobacteria was markedly inhibited by TMDU3 and LA066, respectively. Similarly, treatment of each mAb with neutrophils reduced the numbers of intracellular MAC. Together, our results suggest that the interaction of LacCer-enriched lipid microdomains with mannan core and its blocking are therapeutic or diagnostic targets for both TB and non-tuberculous mycobacteria infection.